On the taxonomic structure and variability of Macropsidius involutus Dlabola, 1963 (Homoptera: Cicadellidae: Macropsinae)—morphology and calling signal pattern - Tishechkin, Dmitri Yu. (Zootaxa, 2018)
Variability of genitalia shape and male calling signal pattern in Macropsidius involutus from 10 localities in South-eastern Europe (the Crimea, the Lower Volga Region), Kazakhstan, and Kyrgyzstan was investigated. Variability of pygofer processes, penis shape, and signal pattern clearly has a geographic component, but none of these traits clearly supports subdividing this species into different subspecies unequivocally. M. involutus was found at altitudes from 0 up to ca. 2000 m a. s. l. in steppes and deserts in the plains and in steppe zones of mountains. Apparently, different environmental conditions in different parts of its range led to divergence of local populations, but the absence of zoogeographical barriers between them makes possible gene exchange and thus prevents emergence of clearly delineated subspecific taxa.